HPLC profile and antihyperglycemic effect of ethanol extracts of Andrographis paniculata in normal and streptozotocin-induced diabetic rats - Ahmad, Mariam; Kasmuri, Abdul Razak; Akowuah, Gabriel Akyirem; Asmawi, Mohd Zaini; Ismail, Zhari (Springer, 2007)
Andrographis paniculata is a Malaysian traditional herb for treatment of fever-causing diseases and diabetes. The aim of the present study was to examine the antihyperglycemic effects of different extracts (95, 50, and 20% ethanol extracts and water extracts) of A. paniculata in normal and streptozotocin-induced diabetic rats. Only the treatment with 20% ethanol extract (at 1 g/kg for 7 h, p.o.) significantly (P < 0.01) reduced the rise in blood glucose levels in glucose-loaded rats. None of the different extracts (at 1 g/kg for 7 h, p.o.) significantly (P > 0.05) altered the blood glucose levels in normal and streptozotocin- induced diabetic rats as compared to the control group. However, administration of the 50 and 95% ethanol extracts (at 1 g/kg for 14 days, p.o.) significantly (P < 0.05) reduced fasting blood glucose and insulin levels in normal and diabetic rats compared to the pre-treatment level. HPLC profiles of the extracts were developed using andrographolide (AP) as a marker. The amounts of AP in 95, 50, and 20% ethanol extracts and water extracts were 25.8, 19.4, 2.0, and 0.8 mg/g of dry weight, respectively.